THE TEACHING OF ENGLISH USING SHORT VIDEO FOR VOCATIONAL HIGH SCHOOL STUDENTS - Kharisma Indriana; Agus Gozali; Moh. Hasbullah Isnaini (IKIP Siliwangi, 2023)
Learning English as a foreign language is a challenge for Indonesian students. Students often find it difficult to develop their English skills. At present, the use of eye-catching and valuable multimedia needs to be implemented intensively to support the teaching and learning process in English classes. This research purpose is to describe the use of short videos as the media in teaching and learning activities in the classroom. This research used the case study method, with an interview and observation checklist as the instruments. Ten key questions in the interview about three aspects that were focused on namely learning experiences, challenges, and benefits of short videos used in class with six students taken by purposive sampling and observation checklist were conducted in the first-year students of Vocational High School 2 Batu at analytical chemistry major class. The results of the study show that the use of short videos in English class presented an interesting and enjoyable learning experience with visuals, subtitles, and clear sound. Short video help students to get a clearer picture of the material so it can be easier to remember and improve their pronunciation, and reading, and introduce them to a lot of new vocabulary. Short videos can be a fun and useful learning medium for students learning English. Keywords: Learning English; Multimedia; Short Video